Web-assisted laboratory for control education : remote and virtual environments - Leão, Celina Pinto (2012)
The Web Assisted Laboratory for Control (WALC) engineering on- line education is described. This on-line platform was developed by a multidisciplinary team. WALC enables the access to several virtual and remote labora- tories experiences on automation, process control and numerical methods. The virtual environment enables the registered user to test different control systems (hydraulic, mechanical, electrical) working in open and close loop. This environment is simulated based on the numerical solutions of the differential equations that describe the real world systems. An industrial automation network is available allowing the user to test different programs running on PLCs. The re- mote access to the platform is confined to pre-registered users and under a booking system ensuring that only the registered user is on-line. Other functionality are depicted. Based on user’ feedback analysis, and since this platform was developed as a dynamic learning tool, their needs are fulfilled.